Sources of Intelligibility of Distant Languages: An Empirical Study. - Milička, Jiří; Marklová, Anna; Láznička, Michal; Diatka, Vojtěch; Bednářová, Hana; Matela, Jiří; Škrabal, Michal (Language & Speech, 2026)
Research into iconicity, systematicity, and sound-symbolism has revealed that the connection between linguistic form and meaning is not completely arbitrary. In the present study, native Czech speakers, unfamiliar with Hindi, were presented with a task in which they had to match Hindi words with their corresponding Czech translations. The words were randomly selected from a Hindi corpus. Despite the considerable linguistic gap between the two languages, the analysis showed that the Czech participants were able to accurately discern the meanings of approximately 60% of the Hindi word pairs, surpassing the 50% success rate that would be expected by random guessing alone. This experiment was subsequently replicated using Turkish, Japanese, and Latvian words, demonstrating the robustness of this phenomenon across different languages. In the case of a closer language like Latvian, the success rate reached 80%. However, even a distant language such as Japanese reached the 60% success level. Furthermore, the study explored potential factors influencing intelligibility. Data collected from a total of 1,128 participants found that the phonological similarity of Czech words and their translation, word length alignment, presence of cognates, and the way the trials were presented had a significant effect on the success rate of guessing the correct translation across all four languages. In addition, language-specific effects were identified.